The role of contract type in soil-improving investments: evidence from rice-planting large-scale production units in China. (17th August 2020) - Li, Fang; Feng, Shuyi; Lu, Hualiang; Qu, Futian; D'Haese, Marijke
Abstract: The emerging large-scale production units (LSPUs) have become increasingly important in Chinese agricultural production and rural transformation due to rapid industrialization and urbanization. Based on household and plot-level data from Jiangsu and Jiangxi Provinces in China, this study provides insights into the farming systems of these LSPUs and examines how contract type, as a proxy for land tenure security, impacts on the production unit's soil-improving investments. Results from the two-stage control function approach show that the written nature of contracts positively affects the application of organic fertilizer and green manure on rented-in plots. Descriptive analysis also confirms the collateralization effect of contract type by showing that plots that are used as collateral for credit are characterized by written contracts. Policies facilitating LSPUs' access to farmland with more formal contracts may therefore play an important role in improving soil quality and land productivity.